The baby tree - Blackall, Sophie (Nancy Paulsen Books, an imprint of Penguin Group (USA), 2014)
After learning that his parents are expecting a baby, a young boy asks several people where babies come from and gets a different answer from each before his parents have a chance to give the right answer. Includes advice on answering questions about reproduction.